IMPROVING METHODS FOR ENRICHING NEW GENERATION TEXTBOOKS WITH MODERN SKILLS. - Muhammad Yunus Azam (TADQIQOTLAR, 2025)
Annotation: This article explores innovative methods for integrating modern skills, such as digital literacy, critical thinking, and collaboration, into next-generation textbooks.  By  combining  insights  from  educational  research  and  technological advancements, it proposes a framework for designing textbooks that prepare students for 21st-century challenges. The study includes a literature analysis, proposed methods, results  from  a  pilot  implementation,  and  recommendations  for  future  textbook development.